Panjang Dan Bobot Saluran Cerna Ayam Broiler Yang Mendapat Ransum Mengandung Herbal Kunyit - Fitriana Akhsan; Muhammad Akbar (Faculty of Agriculture, Musamus University, 2020)
ABSTRACT This research was conducted to see the differences in the length and weight of digestive tract that given turmeric herbs through feed and drinking water. The chickens used were 96 DOC Cobb strains, 8 chickens for each experimental unit. This study used a randomized design with 3 treatments and 4 replications. The treatment arrangements were: T0 = basal feed, T1 = basal feed + 2% turmeric from the amount of feed consumption and T2 = basal feed + 2% turmeric from the amount of drinking water consumption. The parameters observed in this study were the length and weight of of digestive tract the namely the small intestine, large intestine, appendix and bile. Length and weight of the digestive tract (small intestine, large intestine, gizzard), (P <0.05) by offering a feed containing turmeric herbs. The effect of the treatment was not seen on the parameters of length and weight of broiler Cobb strain. The conclusion of this study was that giving turmeric through feed and drinking water at a level of 2% increased the length and weight of the digestive tract.